2017
DOI: 10.1186/s12951-017-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanoparticles: understanding the mechanisms behind antibacterial activity

Abstract: As the field of nanomedicine emerges, there is a lag in research surrounding the topic of nanoparticle (NP) toxicity, particularly concerned with mechanisms of action. The continuous emergence of bacterial resistance has challenged the research community to develop novel antibiotic agents. Metal NPs are among the most promising of these because show strong antibacterial activity. This review summarizes and discusses proposed mechanisms of antibacterial action of different metal NPs. These mechanisms of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,090
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,877 publications
(1,122 citation statements)
references
References 94 publications
26
1,090
3
3
Order By: Relevance
“…This was comparable to the finding of Slavin et al . () who found that the bacterial cell wall was destroyed with subsequent penetration of nanoparticles. Further studies are needed to examine the possibility of using the isolated bacteria in in situ bioremediation of sites contaminated with molybdate along with other contaminants such as iron, chromium, uranium etc.…”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to the finding of Slavin et al . () who found that the bacterial cell wall was destroyed with subsequent penetration of nanoparticles. Further studies are needed to examine the possibility of using the isolated bacteria in in situ bioremediation of sites contaminated with molybdate along with other contaminants such as iron, chromium, uranium etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Mo and co-workersp repared Pd@Ag NSs by reducing Ag + on the surface of Pd NSs. [63] The synthesized NSs showed ah exagonal plate-like structure with an average diameter of about 85 nm ( Figure 4). It was demonstrated the Pd@Ag NSs exhibited an outstanding photothermal conversion effect and could releaseA g + to damaget he bacterial cell membraneu pon exposure to NIR irradiation at l = 808 nm.…”
Section: Metal-based Antibacterial Nanomaterialsmentioning
confidence: 99%
“…On the other hand, absorbed light triggers Ag NPs to release Ag + , which enhances the photothermal disinfection performance . It has been reported that the dissolution of NPs depends on their size, shape, and surface morphology . Moreover, different metal NPs showed different antibacterial performances.…”
Section: Antibacterial Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations